2019
DOI: 10.1002/cbin.11165
|View full text |Cite
|
Sign up to set email alerts
|

Human placenta‐derived mesenchymal stem cells inhibit apoptosis of granulosa cells induced by IRE1α pathway in autoimmune POF mice

Abstract: Previous studies have shown that the ovarian failure in autoimmune‐induced premature ovarian failure (POF) mice could be improved by the transplantation of human placenta‐derived mesenchymal stem cells (hPMSCs); however, the protective mechanism of hPMSCs transplantation on ovarian dysfunction remains unclear. Ovarian dysfunction is closely related to the apoptosis of granulosa cells (GCs). To determine the effects of hPMSCs transplantation on GCs apoptosis, an autoimmune POF mice model was established with zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…The same study also revealed that the PI3K/Akt signaling pathway contributes to the effects of PMSC transplantation on ovarian function (124)(125)(126). Another study reported that PMSC transplantation decreased GCs apoptosis through inhibition of the endoplasmic reticulum (ER) stress inositol-requiring enzyme 1 (IRE1) signaling pathway, thereby improving ovarian structure and function in POF mice (127). Furthermore, PMSC transplantation was shown to improve ovarian function in ovariectomized rats by inducing the production of estrogen and the expression of folliculogenesis-related genes (128).…”
Section: Amniotic Fluid Stem Cells (Afscs)mentioning
confidence: 84%
“…The same study also revealed that the PI3K/Akt signaling pathway contributes to the effects of PMSC transplantation on ovarian function (124)(125)(126). Another study reported that PMSC transplantation decreased GCs apoptosis through inhibition of the endoplasmic reticulum (ER) stress inositol-requiring enzyme 1 (IRE1) signaling pathway, thereby improving ovarian structure and function in POF mice (127). Furthermore, PMSC transplantation was shown to improve ovarian function in ovariectomized rats by inducing the production of estrogen and the expression of folliculogenesis-related genes (128).…”
Section: Amniotic Fluid Stem Cells (Afscs)mentioning
confidence: 84%
“…Another therapeutic mechanism to prevent ovarian failure is to inhibit GC apoptosis. hPMSCs can inhibit GC apoptosis by modulating stress levels controlled by the IRE1α pathway [35]. One of the newest therapeutic approaches is to use stem cells extracted from human menstrual blood.…”
Section: Potential Therapeutic Effectsmentioning
confidence: 99%
“…Accumulating research has confirmed that POF is related to accelerated follicular atresia, which primarily results from the apoptosis of GCs. [ 41 ] Excessive apoptosis can lead to a variety of ovarian diseases, including POF. [ 42 ] To further investigate the antiapoptotic mechanism of RA, the expression of cytochrome c and caspase‐3 was detected by western blot analysis and IHC.…”
Section: Discussionmentioning
confidence: 99%